Post-education-for-all and sustainable development paradigm structural changes with diversifying actors and norms - Yamada, Shoko (International perspectives on education and society,, 2016)
As the target year of achieving Education for all (EFA) development goals approached in 2015, there were growing discussions about the post-EFA agenda in the international community of educational development. Regardless of the magnitude of discourse, this transition from EFA should not be understood simply as a normative framework.It has coincided with fundamental changes in structure, actors, modes of interactions, and practices. The emergence of new types of donors who used to be recipients of aid is changing the landscape of international educational development. Being outside of the self-regulating community of traditional donors, they bring different logics and motivations to this field that often go beyond the frame of meaning making among traditional donors. Further, the networks of civil society actors are increasing their influence on the strategies and principles of international educational development, through their global web of mission-driven and expertise-based advocacy.